IMPACT OF COVID-19 ON PEOPLE LIVING WITH HIV IN MADAGASCAR: A SARS-COV2 SERO-PREVALENCE SURVEY - RAKOTOMALALA, Fetra Angelot; Randriarimanana, Santatriniaina Dauphin; Randriamananjara, Hajanirina Nathanaella; Babin, François Xavier; Randriantsarac, Haja; Tahinamandranto, Tahinamandranto; Rakoto, Danielle Aurore Doll; Samison, Luc Hervé; Ayouba, Ahidjo; Nerrienet, Eric (African Journal of Infectious Diseases (AJID), 2023)
Background: In Madagascar, no study has reported the impact of COVID-19 on people living with HIV (PLHIV). The present work aimed to analyze the seroprevalence of SARS-CoV-2 in Malagasy PLHIV before and during the three waves of COVID-19 pandemic.This is a retrospective study. Materials and Methods: We conducted a retrospective serological survey in PLHIV followed up for HIV viral load (VL) monitoring at the Centre d’Infectiologie Charles Mérieux Madagascar (CICM) between June 2019 and April 2022. The presence of IgM and/or IgG antibodies against SARS-CoV-2 nucleoprotein was detected using a rapid diagnostic test (COVID-PRESTO®). Results: A seroprevalence of 2.5% was found in the 877 patients tested before March 2020, compared to 25.4% (512/2,011) between March 2020 and April 2022. This seroprevalence was 21.7%, 22.3% and 60.1% after the first, second and third waves of COVID-19, respectively. We observed a marginally significant difference (p = 0.043) in SARS-CoV-2 seroprevalence between patients on highly active antiretroviral therapy (HAART) (27.5%) and those who were not (23.7%). No statistically significant difference was observed between PLHIV with undetectable HIV VL (27.4%) and the different detectable VL categories (p>0.05). Conclusions: Our data show the presence of antibodies to SARS-CoV-2 among PLHIV as early as December 2019 in Madagascar. At least 25.4% (512/2,011) of Malagasy PLHIV have been in contact with SARS-CoV-2 since March 2020. There is no significant relation between HIV-1 VL and SARS-CoV-2 seroprevalence. Additional studies with more robust assays in the general population are needed for a detailed knowledge of SARS-CoV-2 impact in Madagascar.